Difference between revisions of "1971 AHSME Problems/Problem 32"

(Problem 32)
(Solution)
Line 6: Line 6:
  
 
== Solution ==
 
== Solution ==
 +
 +
First, we write the expression as <math>(1+sqrt(2))</math>

Revision as of 22:39, 16 August 2019

Problem 32

If $s=(1+2^{-\frac{1}{32}})(1+2^{-\frac{1}{16}})(1+2^{-\frac{1}{8}})(1+2^{-\frac{1}{4}})(1+2^{-\frac{1}{2}})$, then $s$ is equal to

$\textbf{(A) }\textstyle{\frac{1}{2}}(1-2^{-\frac{1}{32}})^{-1}\qquad \textbf{(B) }(1-2^{-\frac{1}{32}})^{-1}\qquad \textbf{(C) }1-2^{-\frac{1}{32}}\qquad \\ \textbf{(D) }\textstyle{\frac{1}{2}}(1-2^{-\frac{1}{32}})\qquad  \textbf{(E) }\frac{1}{2}$

Solution

First, we write the expression as $(1+sqrt(2))$

Invalid username
Login to AoPS